DIFFERENT EFFECT OF SHIFT WORK ON FATIGUE AND WORK RELATED STRESS IN EMERGENCY ROOM NURSES AT THE HOSPITALS IN BADUNG AND DENPASAR REGENCY, BALI, INDONESIA - Juniartha, I Gusti Ngurah; Sardjono, Teguh Wahju; Kartikawatiningsih, Dewi (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Shift work is a way to maintain proper health care daily at hospital. Shift work may affect fatigue level of nurse and work related stress in Emergency Room (ER) nurses. Generally there are two types of shift work, such as two and three division time a day. The three-division time shift includes 6-6-12 shift and 7-7-10 hours shift, and two-division time includes 12-12 hours shift. Lack of studies discusses about shift work on fatigue and work related stress in ER nurses.Objective: The aim of this study was to identify the differences of the effects between 6-6-12 shift, 7-7-10 shift, and 12-12 shift on fatigue and work related stress, and determine the dominant indicator influencing fatigue and work related stress in emergency nurses at the hospitals in Badung and Denpasar regency, Bali Indonesia.Methods: This was an observational analytic study with cross sectional approach. Purposive sampling was done to recruit 102 nurses from eight emergency departments at Badung and Denpasar regency. Occupational Fatigue Exhaustion Recovery (OFER) questionnaire was used to measure fatigue, and Expanded Nursing Stress Scale (ENSS) questionnaire was used to measure work related stress. Univariate analysis was used to analyze demographic characteristics of each ER. Kruskall-Wallis test with post hoc Mann Whitney were used to determine the different score of fatigue and work related stress between each group, and Structural Equation Modeling (SEM) was used to identify contribution of fatigue toward work related stress of ER nurses. Results: There were significant difference of the effect of shift work on fatigue, between 6-6-12 shift and 12-12 shift with p = 0.037, and between 7-7-10 shift and 12-12 shift with p = 0.003; and significant difference of the effect of shift work on work related stress, between 6-6-12 shift and 12-12 shift with p = 0.474, and between 7-7-10 shift and 12-12 shift with p = 0.128. SEM results show that fatigue contributed about 61% to increase work related stress in ER nurses.Conclusion: There was significant difference of the effects on fatigue between two and three-division time of shifts, and there was no difference of the effect on work related stress for each group. Fatigue statistically increased work related stress in ER nurses.